To Makaka di Persimpangan Zaman: Pola Kepemimpinan Tradisional dalam Merawat Tradisi dan Membangun Masyarakat pada Era Modernisasi di Kabupaten Luwu Utara (Studi Etnografi) - Nurlidiawati (Al-Hikmah Journal for Religious Studies, 2025)
This study examines the role of To Makaka as a traditional leader in maintaining tradition and building society in the modern era in North Luwu Regency. The method used is descriptive qualitative with historical, anthropological, and sociological approaches. Data were collected through interviews with traditional, religious, and community leaders, as well as literature reviews. The results show that the To Makaka system has its roots since the establishment of the Luwu Kedatuan in the 10th–13th centuries. The king is positioned in the center, with representatives in areas such as Bua (maddika), Baebunta (makole), and its derivative areas such as Masamba and Uraso which are led by To Makaka. Elections are carried out democratically through seven regions (kombong pitu). Customary law is still used in matters of marriage, death, and social violations, despite facing challenges such as urbanization, juvenile delinquency, and technological advances. To Makaka leadership is still relevant in maintaining social harmony. This study provides a basis for the involvement of traditional leaders in local development and the importance of revitalizing traditional roles amidst the flow of modernization.